CHARACTERISTICS OF CLINICAL MANIFESTATIONS IN POSTCHOLECYSTECTOMY SYNDROME - Bobosher A. Mardonov, (Central Asian Journal of Medicine, 2025)
The study was conducted on the basis of data obtained from a survey of 464 patients who underwent surgery to remove the gallbladder due to cholelithiasis. To develop a clinical classification of PCES and create an algorithm for examining these patients, the results of clinical, laboratory and instrumental studies of 388 patients who underwent inpatient treatment at the multidisciplinary clinic of Samarkand State Medical University in the period from 2018 to 2023, who were diagnosed with “Postcholecystectomy syndrome”, were analyzed. , selected by random sampling. This work is a comprehensive study of postcholecystectomy syndrome (PCES) associated with postoperative consequences of laparoscopic cholecystectomy. The work analyzes clinical variants of PCES, including dyspeptic, pain, icteric, asymptomatic and Charcot variant. Particular attention is paid to the differential diagnosis between functional and structural disorders of the biliary tract using the concentration of cholecystokinin in blood serum. The study also discusses the significance of the lithogenic properties of bile, changes in humoral regulation and exocrine liver disorders in the formation of PCES. The work emphasizes the need for clinical monitoring and correction of biliary insufficiency in patients after cholecystectomy.